2002
DOI: 10.1177/073428290202000403
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Relative Effects of Interventions in Students with Mild Disabilities: Assessing Instructional Time

Abstract: Assessment data are used to make treatment recommendations for students with mild disabilities. However, no assessment procedures exist that allow one to predict with certainty that one academic intervention will be more effective than another academic intervention for a particular student with mild disabilities. Therefore, hypotheses regarding intervention effectiveness should be tested by assessing students' learning rates under different instructional procedures. In this demonstration, alternating treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
99
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 53 publications
(101 citation statements)
references
References 22 publications
2
99
0
Order By: Relevance
“…Research has consistently shown that efficiency data should be used to evaluate and select interventions (Cates et al, 2003;Skinner et al, 1995Skinner et al, , 1997), but the current findings suggest that maintenance should at least be considered in addition to rate of initial learning, which has direct implications for practice and future research. Several limitations should be considered, however.…”
Section: Discussionmentioning
confidence: 71%
“…Research has consistently shown that efficiency data should be used to evaluate and select interventions (Cates et al, 2003;Skinner et al, 1995Skinner et al, , 1997), but the current findings suggest that maintenance should at least be considered in addition to rate of initial learning, which has direct implications for practice and future research. Several limitations should be considered, however.…”
Section: Discussionmentioning
confidence: 71%
“…By identifying components that cause increases in fluency and assessing the time required for each component, researchers may be able to adapt DPR to allow for greater increases in math fluency, while requiring less instructional time (e.g., eliminating time-consuming components that account for little or no learning, applying more time to components that cause the most rapid increases in learning rates). Additionally, to help prevent basic skill deficits from hindering future learning, researchers should compare DPR with other efficient and sustainable interventions so that educators can select interventions that remedy skill deficits as rapidly as possible (Skinner, 2008;Skinner, Belfiore, & Watson, 1995/ 2002.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, I made this mistake when I conducted a comparative effectiveness study (see Skinner, Johnson, Larkin, Lessley, & Glowacki, 1995). Before you judge me too harshly consider that I attempted to correct my mistake when I reanalyzed these data (see Skinner, BelÞore, et al, 1995).…”
mentioning
confidence: 91%
“…As it is, researchers who are attempting to validate and compare strategies and procedures designed to promote learning may be unintentionally disseminating misleading information promoting interventions that hinder student development because they are neglecting to measure learning rates (Cates et al, 2003;Joseph & Nist, 2006;Nist & Joseph, 2008;Skinner, 1998Skinner, , 2008Skinner, BelÞore, & Watson, 1995;Skinner, Fletcher, & Henington, 1996).…”
mentioning
confidence: 97%